2012
DOI: 10.1007/s00299-012-1368-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant activity of leafy vegetables and beans with myoglobin method

Abstract: KEY MESSAGE : Antioxidant activity of seven leafy vegetables and four beans against five reactive oxygen species and reactive nitrogen species was clearly characterized with a protocol using myoglobin as a reporter probe. Antioxidant activity of seven leafy vegetables and four beans against peroxyl radical, hydroxyl radical, hypochlorite ion, and peroxynitrite ion has been measured using myoglob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Essential roles for AP2/ERF TFs (AP2/ERFs) in the response to abiotic (drought, salt, and temperature) and biotic stress factors have been demonstrated for numerous plant species, such as rice, tobacco, and tomato (Pan et al, 2012 ; Zhang et al, 2013 , 2014 ; Wu et al, 2014 ). In addition, some AP2/ERFs, ORA47 (Pauwels et al, 2008 ) in Arabidopsis thaliana and RAV1 (Himi et al, 2011 ) in wheat, were reported to have the possibility of interaction with genes of biosynthesis of lignins and flavonoids.…”
Section: Introductionmentioning
confidence: 99%
“…Essential roles for AP2/ERF TFs (AP2/ERFs) in the response to abiotic (drought, salt, and temperature) and biotic stress factors have been demonstrated for numerous plant species, such as rice, tobacco, and tomato (Pan et al, 2012 ; Zhang et al, 2013 , 2014 ; Wu et al, 2014 ). In addition, some AP2/ERFs, ORA47 (Pauwels et al, 2008 ) in Arabidopsis thaliana and RAV1 (Himi et al, 2011 ) in wheat, were reported to have the possibility of interaction with genes of biosynthesis of lignins and flavonoids.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants have been found to be the bioactive compounds in most medicinal plants [18] . Flavonoids exert antioxidant activity by acting as free radical scavengers through the donation of a hydrogen atom [19] .…”
Section: Discussionmentioning
confidence: 99%
“…The lycopene and β-carotene content of tomatoes may also be helpful in the prevention of arterial diseases [89]. Similarly, beans may be helpful in the regulation of blood sugar and cholesterol levels to an appreciable extent [90][91][92].…”
Section: Rosmentioning
confidence: 99%